Homologous Viral Interference in Aedes albopictus Cultures Chronically Infected with Sindbis Virus - Stollar, Victor (1973)
Complete homologous interference is demonstrated in cultures of Aedes albopictus cells chronically infected with Sindbis virus. The interference occurred before there was any detectable RNA synthesis by the superinfecting virus.